(untitled) (Journal of the Bangladesh Agricultural University, 2020)
BARI mustard-14 variety is a prominent mustard variety that is gradually accepted by the farmers of Bangladesh and generating higher income through farming. The focus of this study was to assess socioeconomic factors determining farmers’ decisions to adopt BARI mustard-14. Primary data were collected through multistage random sampling technique from 76 BARI mustard adopters and 74 non-adopters from selected areas. Mean, percentage, standard deviation and Probit model was used. It was found that the rate of adoption of BARI mustard-14 was 38.95% at farm level but adoption rate was higher in Tangail compared to Cumilla and Rajshahi districts. Bangladesh Agricultural Research Institute (BARI) recommended practices showed that the adoption of different management techniques is low. Probit model showed that education of the farmer, farm size, availability of seed and influence of Sub Assistant Agriculture Officer (SAAO) enhanced the adoption of BARI mustard-14 variety. Profitability analysis showed that the yield of BARI mustard-14 variety is much higher compared to BARI old variety (Tori-7). The average net return of BARI mustard-14 variety was Tk. 14,450 per ha which was also significantly higher (20.77%) than BARI old mustard variety. The BCR of improved variety (1.23) was significantly higher (85.58%) compared to that of old variety. The policy should be targeted to ensure availability of seed and established linkage between extension agent and farmers to get information regarding BARI mustard-14 production and its technology. J Bangladesh Agril Univ 18(1): 180–188, 2020 https://doi.org/10.5455/JBAU.94761